Solar-blind UV photodetector with low-dark current and high-gain based on ZnO/Au/Ga2O3 sandwich structure. (May 2022) - Wang, H.; Ma, J.; Cong, L.; Song, D.; Fei, L.; Li, P.; Li, B.; Liu, Y.
Abstract: High performance ultraviolet photodetectors (UV PDs) have attracted significant attention due to their great potential applications in both military and civilian fields. In this work, dual-band ultraviolet PDs with two peak responses at solar blind (255 nm) and near UV (360 nm) region were successfully fabricated by constructing ZnO/Au/Ga2 O3 sandwich structure. The dark current of the ZnO/Au/Ga2 O3 sandwich structure PD was reduced by 35.6 times and 5.9 times in comparison with ZnO/Au and Au/Ga2 O3 MSM PDs, respectively. The responsivity of the ZnO/Au/Ga2 O3 PD to 255 nm light was 336.3 A/W, which is 1443 times higher than that of the Au/Ga2 O3 PD and corresponds to a gain of 1637. While, the responsivity of the ZnO/Au/Ga2 O3 PD to 360 nm light was 21.6 A/W, which is only 1.2 times higher than that of the ZnO/Au PD and corresponds to a gain of 73. Based on the dependence of photocurrent on incident light intensity, the suppression of dark current in the ZnO/Au/Ga2 O3 PD can be attributed to the reduction of the unsaturated bonds and the trap states at the interface of ZnO and Ga2 O3 . The high gain at 255 nm light in the sandwiched PD has been attributed to the migration of the photogenerated hole from Ga2 O3 to ZnO and the higher electron mobility and the longer hole lifetime of ZnO than that of Ga2 O3 . Such ZnO/Au/Ga2 O3 sandwich structure PDs with low dark current and high gain hold promise for developing high performance UVA and UVC dual-band PDs. Graphical abstract: A dual-band UV MSM PD based on ZnO/Au/Ga2 O3 sandwich structure was designed and fabricated. Compared with its ZnO/Au and Au/Ga2 O3 MSM PDs counterparts, the dark current of ZnO/Au/Ga2 O3 sandwich structure PD is reduced by 35.6 times and 5.9 times, respectively. The suppression of dark current of ZnO/Au/Ga2 O3 PD is due to the reduction of the surface and trap states at the interface of ZnO and Ga2 O3 . The ZnO/Au/Ga2 O3 PD exhibits a dual-band detection at 255 nm and 360 nm light. The responsivity and gain of ZnO/Au/Ga2 O3 PD are 336.3 A/W and 1637 at 255 nm light, which is 1443 times higher than that of the Au/Ga2 O3 PD. The responsivity and gain of ZnO/Au/Ga2 O3 PD are 21.6 A/W and 73 at 360 nm light, which is 1.2 times higher than that of the ZnO/Au PD. The high responsivity and gain at 255 nm light in sandwich structure PD has been attributed to the migration of photogenerated hole from Ga2 O3 to ZnO and the high electron mobility and long hole lifetime in ZnO. Such ZnO/Au/Ga2 O3 sandwich structure PDs with low dark current and high gain hold promise for developing high performance UVA and UVC dual-band PDs. Image 1 Highlights: Solar-blind ultraviolet photodetector based on ZnO/Au/Ga2 O3 sandwich structure was fabricated. Compared with MSM structure PDs, the dark current of sandwich structure PD is reduced by 35.6 times and 5.9 times. The sandwich structure PD reveals a responsivity of 336.3 A/W and a gain of 1637 at 255 nm light. The gain in sandwich PD is due to the migration of hole from Ga2 O3 to ZnO and longer hole lifetime in ZnO than that of Ga2 O3 .